PENGARUH SERTIFIKASI SISTEM MANAJEMEN LINGKUNGAN ISO 14001 PADA KINERJA PERUSAHAAN - Zeffa Aprilasani; Chairil Abdini Abidin Said; Tri Edhi Budhi Soesilo; Adis Imam Munandar (Universitas Mercu Buana, 2017)
Abstract. Various studies revealed that ISO 14001 is an integrated environmentalmanagement system which are considered to be capable for improving firms‟environmental and financial performance. This study aims to analyze the effect of ISO14001 Environmental Management System certification on firm‟s environmental andfinancial performance. The samples of the research were ISO 14001 certified firmswhich listed in Indonesia Stock Exchange. Yearly data were collected for the period of2007-2015. The research employed multivariate data panel regression as the mainmethod. The results showed there is no impact from ISO 14001 certification towardsenvironmental performace and no solid evidence that ISO 14001 has an effect on thefinancial performance. In addition, there is an indication that older firms (over 30 yearsold) tend to pursue ISO 14001 certification based on firm‟s characteristics in thesamples.